Sanksi Tindak Pidana Pembunuhan Anak yang Dilakukan oleh Anak Perspektif Hukum Positif dan Hukum Islam - Amini, Nurul Fajriyah; Antasari, Rr Rina; Fikri, Ikhwan (Jurnal Ilmu Syariah dan Hukum (JISYAKU), 2025)
This study was motivated by the prevalence of juvenile delinquency, particularly murder committed by children against other children. The objective of this study was to examine the perspectives of positive law and Islamic law on the imposition of sanctions for such acts. This study employed an empirical juridical approach using primary and secondary data, which were analysed descriptively and qualitatively and presented deductively. The results of the study indicate that, based on Article 81(2) of Law No. 11 of 2012 on the Juvenile Criminal Justice System, a child may only be sentenced to half the maximum penalty applicable to adults. In the case studied, the child was sentenced to 7 years and 6 months in prison for murder under Article 338 of the Criminal Code. From the perspective of Fiqh Jinayah, the act is classified as jarimah qishash because the perpetrator was 15 years old. However, because the judicial process uses the Indonesian legal system, the child was given a ta'zir punishment in the form of imprisonment.